Isolation and Characterization of Novel Bacteriophages to Target Carbapenem-Resistant Acinetobacter baumannii - Yoon-Jung Choi; Shukho Kim; Minsang Shin; Jungmin Kim (MDPI AG, 2024)
The spread of multidrug-resistant Acinetobacter baumannii in hospitals and nursing homes poses serious healthcare challenges. Therefore, we aimed to isolate and characterize lytic bacteriophages targeting carbapenem-resistant Acinetobacter baumannii (CRAB). Of the 21 isolated A. baumannii phages, 11 exhibited potent lytic activities against clinical isolates of CRAB. Based on host spectrum and RAPD-PCR results, 11 phages were categorized into four groups. Three phages (vB_AbaP_W8, vB_AbaSi_W9, and vB_AbaSt_W16) were further characterized owing to their antibacterial efficacy, morphology, and whole-genome sequence and were found to lyse 37.93%, 89.66%, and 37.93%, respectively, of the 29 tested CRAB isolates. The lytic spectrum of phages varied depending on the multilocus sequence type (MLST) of the CRAB isolates. The three phages contained linear double-stranded DNA genomes, with sizes of 41,326-166,741 bp and GC contents of 34.4-35.6%. Genome-wide phylogenetic analysis and single gene-based tree construction revealed no correlation among the three phages. Moreover, no genes were associated with lysogeny, antibiotic resistance, or bacterial toxins. Therefore, the three novel phages represent potential candidates for phage therapy against CRAB infections.